Analyzing the Vehicle Insurance Ecosystem in Estonia using Actor-Network Theory - Sai, Andrew Adjah; Naroznaja, Anna (European Scientific Journal, ESJ, 2018)
This paper focuses on analyzing the vehicle insurance ecosystem in Estonia that integrated Actor Network Theory (ANT) as theoretical lens to investigate potential transformations in the said ecosystem and to gauge the influence of insurance-oriented telematics technology. The paper combined an interpretive approach applied to a case study method. The study offers insights which are useful to facilitate the alignment of insurance-oriented telematics technology and its practical implementation within social systems. This study is one of the first to examine insurance-oriented telematics technology as a socio-technical process in Estonia.